Leadership lessons for engineers - Alsu Makhmutovna Tuktamyshova; Gulnara Rinadovna Gabdrakhmanova; Albert Kharisovich Gilmutdinov (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The purpose of this study is to describe a MSc course aimed at preparing the elite of engineering education, providing knowledge, developing skills and experience that will allow graduates of Master degree programs not only to find a job, but also to build a successful professional career and a happy life consciously. The presented masters course introduces the best practices of leadership development from the rector of KNRTU-KAI, Albert Gilmutdinov (20122021) (based on his book Leadership Lessons), advanced experience in the development of leadership skills from Russian and foreign universities, as well as a unique American teaching methodology aimed at the peculiarities of training engineering personnel. The study reveals the problems of training modern engineering specialists: engineering student negative attitudes (I cannot learn English, it is too difficult to apply for a grant, an interesting job can only be found by acquaintance); inability of young people to answer questions about how to find a job in their life, how to work hard and not get tired, how to become successful and at the same time maintain good relations with people. The team of authors of the course believes that the results of the implementation of the Leadership Lessons project can be of professional interest not only among masters students, but also among all students of engineering schools, increasing the personal activity of students, their demand in the labor market, as well as strengthening ties between employers and the university.